Vitamins and Infusion of Levodopa-Carbidopa Intestinal Gel. (20th January 2022) - Taher, Jennifer; Naranian, Taline; Poon, Yu-Yan; Merola, Aristide; Mestre, Tiago; Suchowersky, Oksana; Kulasingam, Vathany; Fasano, Alfonso
ABSTRACT: Levodopa-carbidopa intestinal gel infusion (LCIG) is an established therapy for advanced Parkinson disease (PD), resulting in a significant improvement of quality of life. With increased LCIG adoption worldwide, potential complications due to abnormal vitamin absorption or metabolism have been reported in these patients. Neurologists are unfamiliar with vitamins physiology and pathophysiological mechanisms in case of their deficiency. Unfortunately, clinical and laboratory guidelines related to vitamin monitoring and supplementation in the context of treatment with LCIG are not available. We herein summarize the current knowledge on three vitamins that are reduced with LCIG therapy reporting on their physiology, laboratory testing, and clinical impact of their deficiency/excess. In addition, we proposed an opinion-based recommendation for clinicians treating LCIG patients. Patients and caregivers should be informed about the risk of vitamin deficiency. Vitamin B12, homocysteine, and methylmalonic acid (MMA) should be tested before starting LCIG, six months after and once/year thereafter. Vitamin B6 and folate testing is not universally available but it should be considered if homocysteine is elevated but MMA and/or total vitamin B12 are normal. Prophylaxis of vitamin deficiency should be started as soon as LCIG is implemented, possibly even before. Dietary recommendations are enough in most patients although a subgroup of patients is at higher risk and should receive Vitamin B12 regularly and cycles of B6. Finally, once diagnosed a vitamin deficiency should be readily treated and accompanied by clinical and laboratory monitoring. Resistant cases should receive non-oral routes of administration and possibly discontinue LCIG, even temporarily.